Identification and preliminary analysis of hub genes associated with bladder cancer progression by comprehensive bioinformatics analysis - Han Wang; Junjie Liu; Yanyan Lou; Yang Liu; Jieqing Chen; Xinhui Liao; Xiuming Zhang; Chengzhi Zhou; Hongbing Mei; Aifa Tang (Scientific Reports, 2024)
Abstract Bladder cancer (BC) is a crisis to human health. It is necessary to understand the molecular mechanisms of the development and progression of BC to determine treatment options. Publicly available expression data were obtained from TCGA and GEO databases to spot differentially expressed genes (DEGs) between cancer and normal bladder tissues. Weighted co-expression networks were constructed, and Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed. Associations in hub genes, immune infiltration, and immune therapy were evaluated separately. Protein–protein interaction (PPI) networks for the genes identified in the normal and tumor groups were launched. 3461 DEGs in the TCGA dataset and 1069 DEGs in the GSE dataset were identified, including 87 overlapping genes between cancer and normal bladder groups. Hub genes in the tumor group were mainly enriched for cell proliferation, while hub genes in the normal group were related to the synthesis and secretion of neurotransmitters. Based on survival analysis, CDH19, RELN, PLP1, and TRIB3 were considerably associated with prognosis (P < 0.05). CDH19, RELN, PLP1, and TRIB3 may play important roles in the development of BC and are potential biomarkers in therapy and prognosis.